Identification of Anti-Collapsin Response Mediator Protein 2 Antibodies in Patients With Encephalitis or Encephalomyelitis - Xu, Kaibiao; Wang, Dongmei; He, Yan; Wang, Shengnan; Liu, Guanghui; Pan, Yue; Jiang, Haishan; Peng, Yu; Xiao, Fenliang; Huang, Yihua; Wang, Qiqi; Wu, Yongming; et al. (Frontiers in Immunology, 2022)
Background and Purpose: Increasing number of autoimmune encephalitis (AE) associated autoantibodies have been successfully characterized. However, many cases of AE remain unexplained on account of unknown antibodies. The aim of the present study was to identify a novel antibody against collapsin response mediator protein 2 (CRMP2) in the suspected AE patients. Methods: A patient’s serum and cerebrospinal fluid (CSF) samples tested negative for known AE antibodies; however, strong immunolabel signals were observed in the neuronal cytoplasm of the cortex, hippocampus and Purkinje cells on rat brain sections. Immunoprecipitation from the rat brain protein lysate followed by mass spectrometry analysis was used to identify the targeting antigen. Western blotting and/or cell-based assay (CBA) with antigen-overexpressing HEK293T cells were used for antibody specificity, epitope, IgG subtype determination and retrospective study. Results: Antibody against CRMP2, a synaptic protein involved in axon guidance, was identified. The immuno-stains of the patient’s samples on rat brain sections were eliminated by pre-absorption with HEK293T cells overexpressing CRMP2. The samples specifically immunoreacted with CRMP2, but not with CRMP1, 3, 4, and 5. The C-terminus of CRMP2 with 536 amino acids contained the epitope for antibody binding. Subtype analysis showed that the anti-CRMP2 antibody was IgG4. Furthermore, screening from 46 patients with neurological disoders and neuro-cytoplasm immunostainings on rat brain sections resulted in the identification of anti-CRMP2 antibodies in a case of encephalomyelitis. The two patients responded well to immunotherapies. Conclusions: This study discovered that a novel anti-CRMP2 antibody was associated with suspected AE, and thus should be included in the testing list for AE.